A rare case of immune-related pseudotumor of ovary mimicking ovarian malignancy - G. K., Poomalar; S., Rajkumar; K., Thara; B. H., Srinivas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
IgG4-related disease (IgG4-RD) is a chronic inflammatory condition affecting various body organs. However, genital tract involvement is rarely reported. A 40 years old reproductive-age woman presented with a solid abdominopelvic mass of 20 weeks size. CECT revealed a large multiloculated solid cystic lesion arising from right adnexa with multiple enlarged lymph nodes and omental thickening with gross right-sided hydroureteronephrosis suggestive of ovarian malignancy stage III. Surprisingly, tumor markers were normal. Intraoperatively, we noticed a 15×15 cm right ovarian mass encasing the right ureter all around and constricting it. The mass was densely adherent to recto-sigmoid and right pelvic wall, which mandated extensive surgery. Histopathological examination with immuno-histo-chemistry (IHC) suggested the diagnosis of IgG4-RD of ovary. Awareness about its occurrence in ovary will help in arriving at the diagnosis which may influence the extent of surgery. Lymphoplasmacytic infiltration with fibrosis in histopathological examination warrants IHC analysis for achieving a diagnosis.